Measuring the inertial properties of a tennis racket - Spurr, J.; Goodwill, S.; Kelley, J.; Haake, S. (Procedia Engineering, 2014)
Simple and bifilar pendulum were used to measure the mass moments of inertia of three tennis rackets. The pendulum setups were filmed using an off-the-shelf camcorder, with a stopwatch in view to provide timing data. The measurement accuracy was assessed using calibration rods of known mass moment of inertia. The simple pendulum method was found to be most accurate (<1.0% difference to theoretical value) when a square profile rod was used as a pivot. The bifilar pendulum was found to be very accurate (0.0% difference to theoretical value) but sensitive to non-parallel support wires. A Babolat Racket Diagnostic Centre (RDC) was assessed using four calibration rods, of known mass moment of inertia. Measurement agreement was greater than 99.0% for mass moments of inertias within the range of 220 - 380 kg·cm2.